Dampak Penggunaan Sistem Informasi Akuntansi terhadap Efektivitas Pengendalian Internal Lembaga Keuangan Mikro Syariah - Irton; Idris Purwanto (At-Tauzi : Jurnal Ekonomi Islam, 2018)
Accounting information system with a computerized based is a system of collecting, storing and accounting data that are used by decision making. Syari’ah micro finance (LKMS) like other business need accounting information system to increase his quality service. The main objective of the study is to examined impact of accounting information systems oninternal control syariah micro finance. This study use a set questionare distributed to LKMS selected in Wonosobo Jateng DIY. The finding show thataccounting information system used has significance impact on internal control mainly improve information control, detection control, and budget control in LKMS.